PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PERKEMBANGAN KOGNITIF PESERTA DIDIK DENGAN BANTUAN AI - Rhidu Arsi Sayekti Adjiani; Aprilia Eka Rahmawati; Fitri Sukaisih; Febrianti Wahyu Puji Lestari; Devita Dwi Hardiana (Universitas PGRI Madiun, 2026)
The development of AI technology has advanced and brought significant changes to the learning process and cognitive development of students. This article examines the positive and negative impacts of AI use, influencing factors, the actual implementation of AI use, and the roles of teachers and students in utilizing AI in learning contexts. Previous literature has found that AI can increase personal learning engagement and efficiency in accessing information, while simultaneously supporting critical thinking and creativity in students. However, dependence on AI leaves students less trained in critical and creative thinking in accordance with their individual potential. Therefore, the role of teachers is crucial in helping students ensure the effective and balanced use of AI. The method chosen is a qualitative approach, collecting journals and other literature sources, which are then analyzed and concluded.This article is expected to minimize the impact of AI use effectively and in a balanced manner and provide a foundation for educators to design safe and balanced AI learning models without diminishing critical thinking and creativity in students.